Rural Community Well-being in Mining-Affected Areas: A Portrait of Socio-Economics, Health, and Agriculture in North Minahasa Regency - Peggy Adeline Mekel; Sammy Rommy Novie Korua (SOSIOEDUKASI, 2025)
This study examines the socio-economic, health, and agricultural conditions of communities in mining-affected villages in North Minahasa Regency, Indonesia, using a comprehensive census of 2,288 respondents across five villages—Tumbohon, Talawaan, Tatelu, Warukapas, and Tatelu Rondor with Klabat Village as a control site. Employing the Sustainable Livelihood Approach (SLA) framework, the research analyzes five key livelihood assets: human, social, natural, financial, and physical capital. Findings reveal a significant shift in livelihoods, with artisanal mining emerging as a primary income source, surpassing agriculture in economic contribution. While access to infrastructure and basic services is relatively adequate, critical vulnerabilities persist in human capital, particularly in education quality and youth school dropout rates linked to mining work. Health indicators show low prevalence of infectious diseases and high Covid-19 vaccination coverage; however, maternal and child health practices such as exclusive breastfeeding and routine immunization remain suboptimal. Nutritional challenges are evident, with low consumption of fruits and vegetables despite sufficient meal frequency. Social capital is structurally present but weakly expressed in collective action, as participation in communal activities is minimal. Financial dependence on informal and extractive sectors, coupled with limited access to formal financial institutions, increases economic vulnerability. The comparison with Klabat Village highlights a development paradox: higher income in mining areas does not equate to greater multidimensional well-being. This research underscores the need for holistic development strategies that strengthen institutional capacity, diversify livelihoods, and prioritize human development over short-term economic gains. The findings provide critical insights for policymakers, corporations, and local governments aiming to foster inclusive and sustainable development in extractive regions